OP0271 Perk Pathway Characterization in Labial Salivary Glands of Sjögren Syndrome's Patients: Could It Be An Adaptive Response?. (15th July 2016) - Bahamondes, V.; Aguilera, S.; Cortés, J.; Castro, I.; Barrera, M.-J.; Urzúa, U.; González, S.; Molina, C.; Leyton, C.; González, M.-J.
Abstract : Background: Labial-salivary-glands (LSG) of Sjögren's syndrome (SS) patients show an altered exocytic route that can induce endoplasmic reticulum (ER)-stress and activate the unfolded-protein-response (UPR) 1, 2 . UPR helps to recover and preserve cellular homeostasis, reducing the load of unfolded proteins in the ER, through various mechanisms of cell survival. UPR is mediated by the activation of IRE1α, PERK and ATF6 sensors.Chronic activation of ER-stress sensors exhibits a time course-kinetics with attenuation of IRE1α pathway and sustained signaling of PERK and ATF6 pathways 3 . We have observed in SS-patients a decrease of IRE1α pathway activity 4 and an increase of ATF6 pathway activity 5 . Objectives: Considering that PERK pathway reduces levels of unfolded proteins by increasing expression of pro-survival or pro-apoptotic components, here our purpose was to evaluate the expression of PERK pathway components and its relation with an adaptive response of LSG from SS-patients. Methods: RNA and proteins were extracted from LSG of 11 SS-patients and 12 controls. Expression of PERK pathway components was determined by q-PCR and Western-blot. Localization was addressed by immunofluorescence. Results: Compared to controls, LSG of SS-patients showed a significant increase of pPERK/PERK ratio but no changes of peIF2α/eIF2α ratio. Also, an increase of ATF4 and CHOP protein levels were observed, which correlated with clinical parameters including scintigraphy and serology. On the contrary, significantly decreased expression of ERO1α, PDIA1 and PDIA4 (proteins involved in protein folding), and NRF2 (transcription factor) protein levels, an additional PERK substrate involved in the response to oxidative stress, were detected. Interestingly, SS-patients showed a significant increase of expression of Xc- system subunits, which is involved in glutathione synthesis. PERK, ERO1α, PDIA1, PDIA4, eIF2α and peIF2α were located in the basal cytoplasm of acinar cells, while eIF2α and peIF2α were also observed in the nucleus. NRF2 localized in cytoplasm and lateral plasma-membrane, next to E-cadherin. Conclusions: PERK pathway is activated in LSG of SS-patients and controls; indicating that both are developing UPR. Considering that ATF4 mediates an integrated response to cellular stress 6, its increased expression in SS-patients and its correlation with clinical data and Xc – expression, suggest that ATF4 could be part of an adaptive response against cellular stress. In addition, expression of ERO1α, PDIA1 and PDIA4 suggests alterations of the protein folding process. Finally, NRF2 protein levels and its location suggest an altered oxidative stress response. References: Barrera MJ, et al. 2013. J Autoimmun 42:7–18. Goicovich E, et al. 2003. Arthritis Rheum; 48(9): 2573–2584. Hetz C. 2012. Nat Rev Mol Cell Biol; 13(2):89–102. Sepúlveda D, et al. 2015. Manuscript under review in Arthritis & Rheumatology. Barrera MJ, et al. Manuscript in preparation. Harding HP et al. 2003. Mol Cell; 11(3):619–33 Acknowledgement: Supported by Fondecyt-Chile [#1120062] (MJG, SA, CM, SG), PhD fellowship Conicyt-Chile (MJB and JC). Disclosure of Interest: None declared